Türkiye Kırsal Dindarlığı Üzerine Bir Pilot Araştırma (Gördes ve Çevre Köyleri Örneği) - Karaşahi̇n, Hakkı (Dinî araştırmalar, 2007)
In this study, we emphasize on the evolution phase of researches which have studied religiosity in Turkey as an empirical fact and also on the analyses and assessments oriented towards the development of rural religiosity measurement. In this study, as a result of factor analysis applied on the data derived from the sampling of Gördes Country and its villages, served to indicate that it was possible to conduct on the rural religiosity measurement by using an instrument of measuring validity and reliability. We have developed an instrument for measuring which is standardized in reliability and validity manner and can yield considerable benefits from the research conducted on the religious beliefs, attitudes and behaviors of communities living in the towns and villages of Turkey